2011
DOI: 10.3109/14767058.2011.561892
|View full text |Cite
|
Sign up to set email alerts
|

Partial molar pregnancy with a chromosomically and phenotypically normal embryo: presentation of an extremely rare case and review of literature

Abstract: We present an extremely rare case of partial molar pregnancy with a chromosomically and phenotypically normal embryo and review of the literature. A 31-year-old nulliparous was referred to us at 30 weeks of gestation due to absence of fetal movements and subsequent ultrasound examination revealed intrauterine demise. Prenatal amniocentesis due to raised maternal serum α-fetoprotein had shown a karyotypically normal female embryo and second trimester ultrasound demonstrated no anatomic abnormalities. Upon induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Moreover, pre‐eclampsia occurred in seven cases, and all of the cases ended in death of the fetus or neonate. The mean gestational age at delivery was 24.5 ± 6.2 weeks; most of the fetuses (14/18) could not live outside the womb . These findings suggest that a singleton, diploid fetus with partial molar pregnancy is associated with high perinatal mortality rates.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, pre‐eclampsia occurred in seven cases, and all of the cases ended in death of the fetus or neonate. The mean gestational age at delivery was 24.5 ± 6.2 weeks; most of the fetuses (14/18) could not live outside the womb . These findings suggest that a singleton, diploid fetus with partial molar pregnancy is associated with high perinatal mortality rates.…”
Section: Discussionmentioning
confidence: 86%
“…Non‐segregation of paternal chromosomes at stage II of meiosis is also a possible mechanism. Despite the existence of these approaches to the differential diagnosis, previous reports of singleton, partial molar pregnancy coexisting with a diploid fetus number 10 cases with diploid placenta as well as five cases with no karyotyping of the placenta . p57KIP2 immunohistochemical staining was not performed in any of the 15 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this high level of hCG and HL, a partial mole was suspected but fluorescence in situ hybridisation (FISH) was normal and the karyotype was subsequently confirmed as 46XY. Although mosaicism and placental mesenchymal dysplasia (PMD) have previously been reported as accounting for some partial moles [6], this was considered unlikely as the placenta demonstrated neither the characteristics of PMD nor any true hydropic or molar changes. The presence of a euploid cell line culture in the karyotype analysis supported these findings.…”
Section: Case Reportmentioning
confidence: 99%
“…Hamanoue et al also reported a twin pregnancy with complete hydatiform mole and preterm labor of a normal neonate (4). Other studies that reported twin pregnancy with hydatiform mole, mentioned a normal fetus such as Papoutsis et al, that reported a partial mole pregnancy with a chromosomically and phenotypically normal embryo, and Copeland et al who had reported dizygotic twin pregnancy with a normal fetus and partial hydatiform mole (5, 6). One of the noticeable facts in studies reviewed was the gender of the fetus which was female.…”
mentioning
confidence: 99%